Fundamentals of nursing : standards & practice - DeLaune, Sue C.; Ladner, Patricia K. (Albany, New York : Delmar Thomson Learning, 2002)
Offering sound presentation of fundamental nursing concepts, and precise coverage of step-by-step clinical procedures, the second edition of Fundamentals of Nursing has been thoroughly revised to reflect the latest developments in current practice. NEW TO EDITION: Coverage of the nursing process has been moved forward, opening with a discussion of Critical Thinking and the Nursing Process. This lays the foundation for the content presented in later chapters. Content related to spirituality and sexuality is emphasized throughout as appropriate so that students may see how these vital aspects affect clients in vital ways. Increased coverage of family and community health concepts - especially in chapter 11 on the legal framework. Home health care content is also emphasized throughout in order to highlight the many arenas of contemporary client care. Coverage of Alternative/Complementary Treatments is highlighted in each chapter, as appropriate, reflecting the author.
Unit I. Nursing Perspective: Past, Present, and Future -- Ch. 1. Evolution of Nursing and Health Care -- Ch. 2. Theoretical Foundations of Nursing -- Ch. 3. Nursing Education and Research -- Ch. 4. Health Care Delivery System -- Unit II. Nursing Process: The Standard of Care -- Ch. 5. Critical Thinking and the Nursing Process -- Ch. 6. Assessme -- Ch. 7. Nursing Diagnosis -- Ch. 8. Outcome Identification and Planning -- Ch. 9. Implementation -- Ch. 10. Evaluation -- Unit III. Therapeutic Nature of Nursing -- Ch. 11. Nursing, Healing, and Caring -- Ch. 12. Therapeutic Communication -- Ch. 13. Client Education -- Ch. 14. Nursing Complementary/Alternative Treatment Modalities -- Unit IV. Individual and Health -- Ch. 15. Health, Holism and the Individual -- Ch. 16. Cultural Diversity -- Ch. 17. Life Cycle -- Ch. 18. Older Client -- Ch. 19. Self-concept -- Ch. 20.
Includes bibliographical references and index.
Keywords: NURSING